UTILIZATION OF TOFU AND SAGO PULP AS ORGANIC LIQUID FERTILIZER AND ITS APPLICATION TO MUSTARD PLANT - Sunarti Sunarti; Romelos Untailawan (EDU SCIENCES JOURNAL, 2020)
Tofu waste and sago pulp are waste that has the potential to pollute the environment because it creates unpleasant aesthetic odors. On the other hand, this second waste still contains nutrients, especially macro nutrients, so it can be used as a material for making liquid organic fertilizer. In this study, both materials were used as liquid organic fertilizer through the fermentation process with the addition of EM4 liquid and the determination of nitrogen and phosphorus elements by the Kjheldal method and spectrophotometry. Based on the research results obtained Nitrogen levels in tofu waste, sago pulp and liquid organic fertilizer in a row: 2.2558%; 0.4236% and 0.0382%. While the phosphorus content in a row: 0.024%; 0.014%; and 0.012%. The results of the application of liquid organic fertilizer on mustard plants gave a tendency to increase plant height, leaf length, leaf width of mustard plants, but there was no addition of leaf blade for 14 days after planting